The mediating effect of self-esteem on sense of coherence and social support in patients with head and face burns (自尊在头面部烧伤患者心理一致感和社会支持的中介效应) - LIN Yiqing (林依青); ZHANG Jianfang (张建芳); FENG Qi (冯绮); LI Liqin (李立勤) (中西医结合护理)
Objective To explore the mediating effect of self-esteem on sense of coherence and social support in patients with head and face burns. Methods A convenient sampling method was used to select 112 patients with head and face burns from November 2017 to August 2021 in the Burn Injury Department of a grade-A hospital in Suzhou. General data questionnaire, Chinese version of Sense of Coherence 13-item scale (SOC-13), Self-Liking/Self-Competence Scale-Revised (SLCS-R) and Social Support Rating Scale (SSRS) were used to investigate them, and structural equation model was used to test the mediating effect. Results The total scores of SLCS-R, SOC-13 and SSRS were (39. 74 ± 7. 81), (56. 61 ± 8. 87) and (38. 79 ± 5. 27) respectively. Pearson correlation analysis showed that sense of coherence was positively correlated with self-esteem (r=0. 473, P<0. 01)and social support (r=0. 670, P<0. 01). There was a partial mediating effect of self-esteem between sense of coherence and social support (β = 0. 217, P< 0. 01). The mediating effect accounted for 37. 4% of the total effect. Conclusion The scores of sense of coherence and social support of the patients are in the low level. Self-esteem plays a part in mediating the sense of coherence and social support. It is suggested that medical workers should take the initiative to evaluate the social resources and support network of patients with head and face, and take corresponding measures to maintain the level of patients' self-esteem, so as to enhance sense of coherence and promote their mental health. (目的 探讨自尊在头面部烧伤患者心理一致感和社会支持之间的中介效应。方法 采取便利抽样法, 选取2017年11月—2021年8月在苏州市某三级甲等医院烧伤科的112例为头面部烧伤患者为调查对象。采用一般资料问卷、中文版心理一致感量表(SOC-13)、二维自尊量表(SLCS-R)和社会支持量表(SSRS)对其进行调查, 采用结构方程模型检验中介作用。结果 头面部烧伤患者的SLCS-R、SOC-13和SSRS总分分别为(39. 74±7. 81)分、(56. 61±8. 87)分和(38. 79±5. 27)分。Pearson相关分析显示心理一致感与自尊(r=0. 473, P<0. 01)和社会支持(r=0. 670, P<0. 01)呈正相关。自尊在头面部烧伤患者心理一致感和社会支持之间存在部分中介作用(β=0. 217, P<0. 01), 中介效应占总效应的37. 4%。结论 本组患者心理一致感得分处于低水平状态, 社会支持得分处于中等偏上水平。自尊在头面部烧伤患者心理一致感和社会支持之间有部分中介作用。建议医护工作者主动评估头面部患者的社会资源及支持网络, 并采取相应措施维护患者自尊水平, 从而提升心理一致感, 促进其心理健康。)